PENGARUH SISTEM OLAH TANAH DAN PENGENDALIAN GULMA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (ZEA mays SACCHARATA STURT.) VARIETAS PARAGON - Karya, Endang Kantikowati, dan Rinda Febrianti (Program Studi Agroteknologi Faperta UNIBBA, 2021)
The aim of this study was to determine the effect of the interaction between the tillage system and weed control on the growth and yield of maize (Zea mays saccharata Sturt.) Paragon variety. The experiment was carried out in Cibalong Village, Ciheulang Village, Ciparay District, Bandung Regency. The time of the experiment was carried out from September to December 2020. The study used an experimental method, with a Randomized Designated Separate Group with a factorial pattern consisting of 2 treatment factors, namely the tillage system and the weed control system. The tillage system consists of TOT (No Tillage), OTMin (Minimum Tillage), OTMax (Maximum Tillage), while the weed control system factors consist of g1 (No Weed Control) g2 (Physical Mechanical Weed Control) g3 (Physical Mechanical Weed Control) Weed Chemically). The results showed that there was no interaction effect between tillage system and weed control on all observed parameters.